Lower semicontinuity of pullback attractors for a singularly nonautonomous plate equation - Da Silva, Ricardo Parreira [UNESP] (My University, 2012)
We show the lower semicontinuity of the family of pullback attractors for the singularly nonautonomous plate equation with structural damping u tt + a(t, x)u t + (-Δ)u t + (-Δ) 2u + λu = f (u), in the energy space H 2 0(Ω) × L 2(Ω) under small perturbations of the damping term a. © 2012 Texas State University - San Marcos.
Keywords: Lower-semicontinuity; Nonautonomous systems; Plate equation; Pullback attractors